2014
DOI: 10.17576/jkukm-2014-26-04
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Properties of Semisolid Welded Joints for AISI D2 Tool Steel

Abstract: The aim of this study is to investigate experimentally the microstructural evolution of the joints using ledeburitic AISI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…In fact, if the temperature increases, activation of atoms will grow. So, subgrain boundary and anile twins can act as main centers of recrystallization nucleation formation and can quickly be formed to accelerate dynamic recrystallization (Mohammed et al 2014). Temperature sensitivity parameter (η a ) expresses temperature effect on steels when strain and strain rate is constant.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, if the temperature increases, activation of atoms will grow. So, subgrain boundary and anile twins can act as main centers of recrystallization nucleation formation and can quickly be formed to accelerate dynamic recrystallization (Mohammed et al 2014). Temperature sensitivity parameter (η a ) expresses temperature effect on steels when strain and strain rate is constant.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a smooth transition from one part to the other is obtained with no evidence of microcracking or porosity. As for the interfacial reactions that occurred during the heating process, these provided elemental diffusion across the interface and the eutectic liquid spread between the joined surfaces to achieve what appears to be good join at the interfaces of both parts of the steel [38,39]. On the other hand, a study of D2-304 joining revealed that a new type of nonequilibrium diffusion interfacial structure was created at the interface of the two different types of steel [40].…”
Section: Semisolid Diffusionmentioning
confidence: 99%
“…In addition, this joining process allows surface-tosurface joining rather than the line-to-line joining of conventional welding. Therefore, it prevents corrosion at the interface of the components and confers Tool steel [14] Stainless steel Aluminum alloy [15] Aluminum alloy, cast iron, or stainless steel Particles, balls, short fibers of metallic or nonmetallic materials, such as ceramic, glass, tile, or stone, aluminum alloy, copper alloy, or stainless steel [5,12,17,18] Stainless steel M2 tool steel [20] X210CrW12, 100Cr6, and X5CrNil18-10 9SMn28, CuCo2Be, CuSn12, and GBZ12 [13,21] Sn-15 wt%Pb Sn-15 wt%Pb Sn-5 wt%Pb [10] Pb-15 wt%Sn Pb-15 wt%Sn [25] Zinc AG40A die cast alloy Zinc AG40A die cast alloy [26] A356 A356 [27] SiCP/A356 composites 2024 aluminum alloy Zn-Al [29] SiCP/A356 composites SiCP/A356 composites Zn-Al [43] AZ91 alloy AZ91 alloy Mg-25 wt%Zn [33] A356 aluminum alloy A356 aluminum alloy [34] D2 tool steel D2 tool steel [39] D2 tool steel 304 stainless steel [40] D2 tool steel M2 tool steel [42] a better shape than welding. Furthermore, SSMJ can be used to embed metallic or ceramic materials for use in reinforcement or as bearing systems [12].…”
Section: Advantages and Disadvantages Of Ssmj Compared To Conventionamentioning
confidence: 99%
See 2 more Smart Citations